The Development of Hallwachs Miracle Novel as a Media Science Literacy in Learning Photoelectric Topic - Purwahida, Rahmah; Yanez, Maria Angelica; Nabilah, Norma (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2023)
This study aims to develop a novel entitled "The Miracle of Hallwachs" as a medium for enhancing scientific literacy, particularly focusing on the physics concept of the photoelectric effect for third-grade high school students. The research employs the Research and Development (R&D) approach, utilizing the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) development model. Data were collected through observation, interviews, and questionnaires, and both qualitative and quantitative analyses were conducted. Product testing involved assessments by material experts, media experts, and 31 students. The study's outcomes resulted in the creation of learning media in the form of audiobooks accessible through various devices. The media's feasibility was evaluated by experts in the field, including material experts, media experts, and Indonesian language teachers, as well as through a field trial with 31 students. Expert validation indicated a high level of appropriateness, with a 97% approval rate for material validation and a 94.29% approval rate for learning media validation. Based on this comprehensive assessment, it can be concluded that the novel under development is well-suited as a medium for enhancing media literacy in science, specifically in teaching physics with a focus on the photoelectric effect.